Infant Feeding Decision-Making and the Influences of Social Support Persons among First-Time African American Mothers - Asiodu, Ifeyinwa V. (Matern Child Health J, 2017)
BACKGROUND: While breast milk is considered the gold standard of infant feeding, a majority of African American mothers are not exclusively breastfeeding their newborn infants. PURPOSE: The overall goal of this critical ethnographic research study was to describe infant feeding perceptions and experiences of African American mothers and their support persons. METHODS: Twenty-two participants (14 pregnant women and eight support persons) were recruited from public health programs and community based organizations in northern California. Data were collected through field observations, demographic questionnaires, and multiple in-person interviews. Thematic analysis was used to identify key themes. RESULTS: Half of the mothers noted an intention to exclusively breastfeed during the antepartum period. However, few mothers exclusively breastfed during the postpartum period. Many participants expressed guilt and shame for not being able to accomplish their antepartum goals. Life experiences and stressors, lack of breastfeeding role models, limited experiences with breastfeeding and lactation, and changes to the family dynamic played a major role in the infant feeding decision making process and breastfeeding duration. CONCLUSION: Our observations suggest that while exclusivity goals were not being met, a considerable proportion of African American women were breastfeeding. Future interventions geared towards this population should include social media interventions, messaging around combination feeding, and increased education for identified social support persons. Public health measures aimed at reducing the current infant feeding inequities would benefit by also incorporating more culturally inclusive messaging around breastfeeding and lactation.